KAJIAN FENOMENOLOGI MAKNA SIKAP KERJA BAGI APOTEKER DI RUMAH SAKIT UMUM DAERAH KOTA MATARAM - Pathiatul Hasanah; Thatok Asmony; Dwi Putra Buana Sakti (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2019)
Pharmacutical service for outpatient that held by pharmacist have not fulfilled the indicator standard of quality service related to quening, waiting time for receiving medicine, the availability of medicine and officers attitude. The research question according to the research problem is how is the pharmacist’ work attitude in doing pharmaceutical service in Region Public Hospital of Mataram City. This study is  a qualitative research by phenomenological approach to  understand the meaning of pharmacist’s work attitude in doing pharmaceutical service in the Region Public Hospital of Mataram City. There were two qualified and competent key informants provided explanation of work attitude meaning of pharmacist’s in terms of outpatient. The study results showed that the pharmacist’s work attitude on outpatient was reflected by four themes, namely : organization commitment, work satisfaction, team work involvement and the perceived organization support. Key words  : Phenomenology, the meaning of work attitude, pharmacist